Financial means to political ends : investment banking contracts in share-issue privatizations - Megginson, William L. ([s.n.] [S.l.], 1994)
Looks at the share offering terms of major privatizations executed by public sale of shares during the period 1961-1993 and examines whether the governments involved were pursuing principally political or financial objectives.